Strategic insider trading: Disguising order flows to escape trading competition - Gu, Dingwei; Liu, Xin; Sun, Hanwen; Zhao, Huainan (Journal of Corporate Finance, 2021)
Short sellers actively exploit trading opportunities from insider sales. We argue that, in response to concern about potential order flow information leakage, insiders strategically disguise their order flows to escape trading competition. Our model predicts that, when short sellers are sensitive to order flow information, insiders are more likely to adopt a cautious trading strategy, i.e., splitting their trades over time. Empirically, we identify cautious trading by tracking consecutive transactions at the insider-strategy level. We find that, when anticipating intensive short selling potential, (1) insiders tend to trade cautiously; and (2) cautious insiders tend to reduce their initial trades. Overall, we highlight the strategic interaction between insiders and short sellers on the diffusion of order flow information.